Faktor-Faktor yang Memengaruhi Minat Masyarakat Berwakaf Uang/Melalui Uang dalam Mendukung Pembangunan Berkelanjutan Kota Bogor - Hilman Hakiem; Irfan Syauqi Beik; Idqan Fahmi (AL-MUZARA'AH, 2022)
Sustainable Development Goals (SDGs) has been interesting issue in this era. One of the ways to support these goals is by empowering cash waqf. The purpose of this research is to identify people perception on cash waqf to support sustainable development in Bogor City, to analyze the factors affecting people interest in cash waqf to support sustainable development in Bogor City, and to create formulas in order to increase the collection of cash waqf to support sustainable development in Bogor City. This research uses descriptive analysis, median analysis, Partial Least Square-Structural Equation Modelling (PLS-SEM) analysis, and strategic analysis. It is found that the most dominant indicator goes to “spending money for the needy can increase the spirit of religion, to support sustainable development”. It is also found that 64.86% indicators are included as good perception. Awareness, knowledge, attitude, and religiosity have positive and significant effect on people interest in cash waqf to support sustainable development in Bogor City, while promotion and socialization have positive effect but not significant. Improving on awareness, knowledge, attitude, and maintain religiosity should be taken as the main strategy to increase the collection of cash waqf to support sustainable development in Bogor City.